Salinity and Drainage in San Joaquin Valley, California Science, Technology, and Policy - Chang, Andrew C.; Brawer Silva, Deborah; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book documents the history of irrigated agriculture and drainage in the San Joaquin Valley, and describes the hydrology and biogeochemical processes of salts and selenium, remediation technologies for salts and trace elements and policy and management options. The contents are comprised of fourteen chapter-length independent treatises, each depicting with fresh perspective a distinctive salinity drainage topic. The opening chapters detail the evolution of irrigated agriculture, and depict the geochemical and hydrological processes that define the San Joaquin Valley, including the physics, chemistry, and biology attributes that impact water management policies and strategies. Next, the contributors address the biogeochemistry of selenium, the role of plants in absorbing it from soils, and the processes involved in retaining and concentrating dissolved salts in drainage water. Further chapters describe on-farm and plot-level irrigation provisions to reduce agricultural drainage outputs and examine their effects on plant performance. This volume offers realistic policy analysis of water management options for irrigated agriculture in the Valley and assesses their respective outcomes, if implemented. Also included is an international perspective on the sustainability of irrigated agriculture there.
Chapter 1: E. W. Hilgard and the History of Irrigation in the San Joaquin Valley: Stunning Productivity, Slowly Undone by Inadequate Drainage -- Chapter 2: Salinity and Drainage Problems and the Framework for a Response -- Chapter 3: Scales and Scaling as a Framework for Synthesizing Irrigated Agroecosystem Research on the Westside San Joaquin Valley -- Chapter 4: Biogeochemistry of Trace Elements: Reactions in Soils -- Chapter 5: Uptake, Metabolism, and Volatilization of Selenium by Terrestrial Plants -- Chapter 6: Microbial Volatilization and Reduction of Selenium -- Chapter 7: Chemistry and Biology of Agricultural Evaporation Ponds -- Chapter 8: Management of Evaporation Basins to Reduce and Avoid Adverse Impacts to Water Birds -- Chapter 9: Integrated Irrigation and Drainage Water Management -- Chapter 10: Drainage water reuse: Concepts, Practices and Potential Crops -- Chapter 11: Membrane Desalination of Agricultural Drainage Water -- Chapter 12: Advances in Wetland Salinity Management -- Chapter 13: Regional Economics and Management in Closed Drainage Basins -- Chapter 14: Beyond California: An International Perspective on Sustainability of Irrigated Agriculture -- Index.
Keywords: Environmental sciences; Hydraulic engineering; Environmental toxicology; Soil conservation; Sustainable development; Environmental economics; Environment; Soil Science & Conservation; Environmental Economics; Hydrogeology; Ecotoxicology; Sustainable Development; Environmental Science and Engineering